Basal metabolic rate and the rate of senescence in the great tit - Bouwhuis, S; Sheldon, B; Verhulst, S (2011)
1. Between-individual variation in rates of senescence has recently been found to relate to natal and early-life conditions in several natural populations. Mechanistic theories of senescence have predicted between-individual variation in basal metabolic rate (BMR) to also underlie such variation in rates of senescence. The question whether variation in BMR is linked to natal and early-life conditions with effects on senescence has, however, not yet been addressed. 2. Using cross-sectional data on winter BMR of nearly 700 individual great tits Parus major, we tested whether factors associated with individual variation in the rate of senescence were also associated with differences in BMR. 3. We found that winter BMR was a repeatable trait (36%), and that variation in winter BMR was partly explained by body mass, and interactive effects of sex, age and seasonal date with ambient temperature. 4. Our data, however, revealed that neither the level of BMR, nor its age-specific decline, was explained by three parameters previously shown to underlie variation in rates of reproductive senescence in our study population: maternal age, immigrant status and early-life reproductive performance. 5. These results therefore did not support the suggestion that variation in BMR underlies variation in rates of reproductive senescence in relation to maternal age, immigrant status and early-life reproductive performance. 6. We further found a low repeatability of BMR from winter to the subsequent breeding season (1%, n=55), which suggested that a relationship between BMR and proxies for rates of senescence may have been absent in our data set because winter BMR did not represent year-round metabolic strategies. 7. Further study, preferably using longitudinal data, is required to resolve the link between BMR at different times of year and senescence. © 2011 The Authors. Functional Ecology © 2011 British Ecological Society.